Lupus-related vasculitis in a cohort of systemic lupus erythematosus patients - Sherif M Gamal; Sally S. Mohamed; Marwa Tantawy; Ibrahem Siam; Ahmed Soliman; Marwa H. Niazy (Archives of Rheumatology, 2021)
Objectives: This study aims to examine the frequency and clinical association of lupus-related vasculitis in patients with systemic lupus erythematosus (SLE). Patients and methods: We retrospectively analyzed medical records of a total of 565 SLE patients (42 males, 523 females; mean age: 32.7±9.5 years; range, 13 to 63 years) between January 2017 and February 2020. Demographic, clinical data, and laboratory data and treatment modalities applied were recorded. Lupus-related vasculitis and its different types were documented, and the patients with vasculitis were compared with those without vasculitis. Results: The mean disease duration was 8.9±6.3 years. Vasculitis associated with lupus was found in 191 (33.45%) patients. Cutaneous vasculitis was found in 59.2%, visceral vasculitis in 34.0%, and both in 6.8% of total vasculitis patients. The patients with vasculitis had a longer disease duration (p=0.01), were more likely to have juvenile onset (p=0.002), livedo reticularis (p<0.001), Raynaud’s phenomenon (RP) (p<0.001), digital gangrene (p<0.001), thrombosis (p=0.003), and cranial neuropathy (p=0.004). The patients with vasculitis showed a higher prevalence of hypercholesterolemia (p=0.045), diabetes mellitus (p=0.026), higher Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) at disease onset (p<0.001), and Systemic Lupus International Collaborating Clinics (SLICC) Damage Index (p=0.003) scores. They had more prevalent hematological manifestations (p<0.001), hypocomplementemia (p=0.007), received a higher cumulative dose of intravenous methylprednisolone (p<0.001), and had also more frequent cyclophosphamide (p=0.016) and azathioprine intake (p<0.001). In the logistic regression analysis, SLE vasculitis was independently associated with juvenile disease onset, livedo reticularis, RP, hematological manifestations, and higher scores of SLEDAI at disease onset (p<0.05). Conclusion: Juvenile disease onset, livedo reticularis, RP, hematological manifestations, and higher SLEDAI scores at disease onset may be associated with the development of vasculitis in SLE patients.